'I didn't feel safe inside': navigating public health advice, housing and living with bushfire smoke. Issue 2 (15th March 2023) - Williamson, Rebecca; Banwell, Cathy; Calear, Alison L.; LaBond, Christine; Leach, Liana S.; Olsen, Anna; Phillips, Christine; Walsh, Erin I.; Zulfiqar, Tehzeeb
ABSTRACT: Bushfires, and resulting bushfire smoke, were major environmental, social and health crises in Australia in the summer of 2019–20. In Australia's national capital the smoke pollution index topped global charts, and public health communications were rapidly developed that advised people to stay indoors to avoid smoke exposure. Drawing on interviews with a diverse range of housed residents, we explore people's experiences of navigating public health advice and managing the bushfire smoke in relation to the materiality of their homes. Given the increasing likelihood of living with such crises in the Anthropocene, we highlight the need for future bushfire public health advice to recognise local housing geographies, residents' embodied vulnerabilities and the relational ways people live with their everyday built environment, and suggest possible policy responses.